ANALYSIS OF PRIMARY SCHOOL STUDENTS’ MISCONCEPTION THROUGH SIX TIER DIAGNOSTIC TEST ABOUT THE CONCEPT OF WATER CHARACTERISTICS - Dewi Renita Sari (Universitas Muhammadiyah Ponorogo, 2018)
Science is knowledge consisting of a collection of concepts. The wrong concept understanding will lead to misconceptions in students. The main purpose of this research is to analyze primary school students’ misconception through six tier diagnostic tests about the concept of water characteristics. This research used descriptive qualitative approach. Data were collected by using six tier diagnostic test. The subjects of this study are the fifth grade students of primary school. Based on the results of data analysis, researchers found that almost half of the students experience the misconceptions on the concept of water characteristics including water gives pressure, soapy water cleans oily dirt, and water dissolves various substances. The six tier diagnostic test instrument show the primary school students’ misconception on the concept of water characteristics. Some factors that cause misconceptions in students are students' prior knowledge, teacher mistaken, and errors in textbooks.